Analysis of Student Learning Difficulties in Islamic Religious Education (PAI) Subjects - Oviyanti, Fitri Oviyanti; Maryamah, Maryamah; Sartika, Anggun; Sanjaya, Cencen Rexsy; Supriyadi, Supriyadi (STAI Miftahul Ula Nganjuk, 2024)
This study aims to describe the mathematics learning difficulties experienced by students as well as internal and external factors in students' science learning difficulties at SDN 3 Bumi Kencana, starting from what are the internal and external learning difficulty factors. This type of research is descriptive qualitative research. This research took the subjects of class teachers and third grade students. The technique in this research is qualitative and the data collection techniques in this research are observation, interview, and documentation. The results showed that the factors that influence students' learning difficulties apart from external and internal factors, namely, where many mistakes are made by students such as being mistaken in reciting the order in prayer. For children with poor memory, it will be difficult to connect one topic with other math topics.